In-vitro Evidence for Novel, Non-Classical, Alternative P450scc-Initiated Vitamin D Metabolic Pathways in Human Placenta via HPLC-UV/DAD and LC-ESI-MS/MS Analysis - Shehabi, Haleem Ziad (Curtin University, 2020)
Current findings identify and substantiate existence of previously unrecognised, likely, in-vivo alternative, non-classical P450scc-initiated vitamin D3/D2 metabolic pathways within in-vitro human placenta models. These pathways are further modified by CYP27A1 or CYP27B1 activity in human placenta and confirmed where required by purified human enzyme studies. This data was closely verified using equivalent in-vitro bovine adrenal cortex models and where necessary by purified bovine enzyme studies. Profiling was achieved by newly developed HPLC-UV/DAD and LC-ESI-MS/MS methodology.